(untitled) (Nigerian Journal of Technology, 2016)
Construction industry is complex in nature because it contains large number of parties such as clients, consultants and contractors. The factors that influence construction management practice differ from country to country, due to prevailing conditions. The objective of this project is to identify factors that influence construction management practice in Nigeria construction industry and elicit perceptions/ranking of the severity using relative importance index of the various factors. A comprehensive literature review was conducted to generate a set of factors believed to influence construction management practice in Nigeria. A questionnaire survey was conducted and fifty-seven (57) factors were identified, grouped into nine (9) categories, evaluated and ranked from the construction actor’s perspectives. 108 questionnaires were distributed to the key construction actors as follows: 45 to contractors, 33 to consultants and 30 to clients. Out of these questionnaires distributed, 92 were received (85%) as follows: 40 (88.9%) from contractors, 28(84.8%) from consultants and 24 (80%) from clients as respondents. The enlarged features included those from both previous Nigerian studies and other related international studies represented in the literature. The degree of agreement between parties regarding the ranking of factors was determined according to Kendall’s Coefficient of Concordance and the survey findings indicate from three target groups (contractors, consultants and clients) agree that the most important factors that influence management of construction projects are as follows: conflicting design information, effective co-ordination of resources, critical path method, materials availability, setting timeliness, civil strife of riots, sense of belonging & identification with the project team, lack of construction management knowledge and known work progress. http://dx.doi.org/10.4314/njt.v35i4.9